Application of Multicultural Education in Social Science Learning in Class V Elementary School - Hamzah Hadis; Abd. Azis Muslimin; Idawati I (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to analyze multicultural education materials in social studies, to analyze the application or relationship between multicultural education in social studies and students' Bugis language behavior, and to analyze the supporting factors or the influence of multicultural education teaching and its application with Bugis language behavior at UPTD SPF SDN 277 Sarecoppeng, Soppeng Regency. Types and Approaches This research is a qualitative research by providing a clear and systematic description related to the object under study in order to provide valid information and data related to facts and phenomena in the field. The main focus in this research is the process and interaction of the subject and the behavior it displays, describes how the subject interacts with his surroundings related to the teaching of multicultural education and its application to the Bugis language behavior of students in social studies at UPTD SPF SDN 277 Sarecoppeng. The results of the study Contextual learning model is a learning model that motivates students to interpret learning by linking existing materials with students' daily lives, through this model, students are introduced that all differences that exist around are a gift from God Almighty so that students familiarize themselves with do not discriminate, understand the perceptions of others, avoid stereotypes, develop equality and social justice. and provide an understanding that with differences, everyone can complement each other. understand the importance of diversity, understand each individual from various racial, ethnic,.